Karyotype and Mapping of Repetitive DNAs in the African Butterfly Fish Pantodon buchholzi, the Sole Species of the Family Pantodontidae - Ráb, Petr; Yano, Cassia F; Lavoué, Sébastien; Jegede, Oladele I; Bertollo, Luiz A C; Ezaz, Tariq; Majtánová, Zuzana; de Oliveira, Ezequiel A; Cioffi, Marcelo B (Cytogenetic and genome research, 2016)
The monophyletic order Osteoglossiformes represents one of the most ancestral groups of teleosts and has at least 1 representative in all continents of the southern hemisphere, with the exception of Antarctica. However, despite its phylogenetic and biogeographical importance, cytogenetic data in Osteoglossiformes are scarce. Here, karyotype and chromosomal characteristics of the lower Niger River population of the African butterfly fish Pantodon buchholzi, the sole species of the family Pantodontidae (Osteoglossiformes), were examined using conventional and molecular cytogenetic approaches. All specimens examined had 2n = 46 chromosomes, with a karyotype composed of 5 pairs of metacentric, 5 pairs of submetacentric, and 13 pairs of acrocentric chromosomes in both sexes. No morphologically differentiated sex chromosomes were identified. C-bands were located in the centromeric/pericentromeric region of all chromosomes and were associated with the single AgNOR site. FISH with ribosomal DNA probes revealed that both 5S and 18S rDNA were present in only 1 pair of chromosomes each, but did not colocalize. CMA3+ bands were observed near the telomeres in several chromosome pairs and also at the 18S rDNA sites. The mapping of di- and trinucleotide repeat motifs, Rex6 transposable element, and U2 snRNA showed a scattered distribution over most of the chromosomes, but for some microsatellites and the U2 snRNA also a preferential accumulation at telomeric regions. This study presents the first detailed cytogenetic analysis in the African butterfly fish by both conventional and molecular cytogenetic protocols. This is the first of a series of further cytogenetic and cytogenomic studies on osteoglossiforms, aiming to comprehensively examine the chromosomal evolution in this phylogenetically important fish order.
Keywords: Animals; RNA, Ribosomal, 18S; ribozomální DNA; Female; DNA, Ribosomal; Chromosome Banding; ženské pohlaví; Afrika; cytogenetické vyšetření; telomery; Telomere; Fishes; Cytogenetic Analysis; transpozibilní elementy DNA; karyotyp; ryby; Phylogeny; DNA Transposable Elements; Male; Africa; Karyotype; RNA ribozomální 18S; Microsatellite Repeats; hybridizace in situ fluorescenční; zvířata; mužské pohlaví; In Situ Hybridization, Fluorescence; fylogeneze; mikrosatelitní repetice; pruhování chromozomů